Satisfaction of caregivers and older adults who use the Better at Home Program - Natália Romana Gomes da Silva; Garibaldi Dantas Gurgel Junior; Domício Aurelio de Sá; Vanessa de Lima Silva; Rafael da Silveira Moreira (Revista de Saúde Pública, 2022)
ABSTRACT OBJECTIVE Evaluate the satisfaction of caregivers and older adults who use the home care service provided by the Better at Home Program (Programa Melhor em Casa) and its associated factors. METHODS This is a cross-sectional study with data from the national survey on the Better at Home Program, conducted by the SUS General Ombudsman. We interviewed 5,595 caregivers and 950 older adults. We combined four questions related to satisfaction to formulate the dependent variable by means of latent class analysis and used 13 questions as independent variables. RESULTS 93.7% of the older adults and 90.2% of the caregivers were satisfied with the service. In the multiple analysis, the variables showing association with satisfaction were: also being accompanied by a family health team (older adults: OR = 4.22; p = 0.014), shorter time between referral and the first visit (older adults: OR = 10.20; p = 0.006), (caregiver: OR = 5.84; p < 0.001), taking examinations with medical requirement (older adults: OR = 5.74; p = 0.037), (caregiver: OR = 7.41; p < 0.001), consultation with specialist (caregiver: OR = 6.02; p < 0.001), visits out of the schedule when necessary (older adults: OR = 8.09; p = 0.014), (caregiver: OR = 1.81; p = 0.015) and understanding the orientations provided by the program team (caregiver: OR = 10.61; p < 0.001). CONCLUSIONS The majority of the older adults and caregivers showed satisfaction with the program, with a distinction in the aspects associated with this satisfaction, in which only the characteristics directly related to the program influenced the satisfaction, while the same did not occur with the socioeconomic and demographic characteristics.